Analisis Kelayakan Bahasa dalam Buku Teks Bahasa Indonesia Kelas VII untuk SMP/MTS Kurikulum 2013 Edisi Revisi 2017 - Mukminati Zulfa; Muhammad Mukhlis; Nur Raudaturrahmah; Nadya Tri Ananda; Nurwahyuni; Muhammad Raihan (UIR Press, 2022)
This study is intended to describe the appropriateness of the language of Indonesian textbooks. The method used in this analysis uses a qualitative descriptive method. This study uses a descriptive method because this research processes data in the Indonesian Class VII textbook for SMP/MTS Curriculum 2013 revised 2017 edition published by the Ministry of Education and Culture for analysis. Qualitative because the data used does not use statistical data, but uses data sourced from documents and book analysis results. Data collected by using book analysis techniques. The data is in the form of linguistic content in the material for Class VII Indonesian textbooks for SMP/MTS Curriculum 2013 revised 2017 edition published by the Ministry of Education and Culture. The results of the analysis of the book are to see and assess the feasibility of the Indonesian Class VII textbook for SMP/MTS Curriculum 2013 revised 2017 edition published by the Ministry of Education and Culture. Based on the results of the analysis that has been carried out, it was found that the level of accuracy of the sentence structure already represents the content of the message and information to be conveyed and does not come out of the discussion in the material while still following the Indonesian grammar.